Persepsi Anggota Organisasi Mahasiswa Extra Kampus di Universitas Medan Area tentang Partisipasi Politik Etnik Tionghoa Menjelang Pemilu 2024 di Kota Medan - Armansyah Matondang; Jaenal Abidin; Ilma Sakinah Tamsil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study examines the social relations between Indigenous and ethnic Chinese in the city of Medan ahead of the 2024 election, this research departs from the reality that in the long span of political upheaval that led to social upheaval in Indonesia, Chinese people are often used as an outlet for anger by the masses. Medan is one of the cities that has a record of incidents where Chinese people were the targets of violence. In every political upheaval there is always the role of extra-campus student organization activists. The purpose of this research is to find out how the perceptions of members of the extra-campus student organization at the University of Medan Area towards ethnic Chinese in Medan city ahead of the elections in 2024. This study uses a qualitative approach with a qualitative descriptive method. The results of the study found, Chinese people who live in the city of Medan ahead of the 2024 general election still tend to be the same as before, and efforts need to be made to encourage assimilation by all ethnicities who live together in the city of Medan.